Interprofessional Leadership Development: Role of Emotional Intelligence and Communication Skills Training - Sneha Shrivastava; Johanna Martinez; Daniel J. Coletti; Alice Fornari (Association of American Medical Colleges, 2022)
Introduction Among the many skills required for leading interprofessional health care teams, emotional intelligence and communication skills are critical to building professionalism, establishing patient trust, and providing optimal patient care. Nonetheless, these skills are often overlooked in medical training. We implemented a 2.5-hour workshop for interprofessional trainees to self-assess, reflect, and apply their emotional intelligence and communication skills. Methods Participants were interprofessional trainees, including internal medicine residents, medical students, and graduate students in clinical pharmacy, physician assistant, and health psychology training programs. The workshop consisted of reflective activities to self-assess emotional intelligence and communication styles; a didactic presentation focused on leadership, emotional intelligence, and communication styles; and a teamwork activity to apply emotional intelligence and communication skills. Results Forty-four trainees participated in this workshop. After the workshop, trainees reported increased knowledge about positive strategies to communicate with team members, felt more comfortable working with other professionals to encourage positive team dynamics, and were more prepared to encourage leadership in their interprofessional teams. Examination of learner evaluations suggested that residents endorsed higher mean ratings than the other learner groups in knowledge attainment (p = .02) and meeting all learners' needs (p = .01). Discussion This workshop enhanced our trainees' self-reported comfort, awareness, and preparedness regarding using emotional intelligence and communication strategies. An interprofessional approach can be beneficial for leadership training in the health professions.